PUAN MAHARANI'S SPEECH AT THE HOUSE OF REPRESENTATIVES (DPR): IN THE RHETORIC STUDY (PIDATO PUAN MAHARANI DI DEWAN PERWAKILAN RAKYAT (DPR): DALAM KAJIAN RETORIKA) - Adrias Adrias; Syihabuddin Syihabuddin; Vismaia S. Damaianti; Andoyo Sastomiharjo (Jurnal Gramatika, 2020)
This research discusses the speech of Puan Maharani at the House of Representatives (DPR) of the Republic of Indonesia in a rhetoric study. The purpose of this study is to describe the nature of Puan Maharani in speaking in terms of language style and in terms of pronunciation and expression techniques. This research is a qualitative descriptive study which is the object of this research is Puan Maharani's speech in the rhetoric study. Data obtained using the method of refer, record and note it. The findings of Puan Maharani's speech in the House of Representatives (DPR) of the Republic of Indonesia in rhetoric studies (1) based on tone, Puan Maharani was found to tend to use a simple style, (2) language style based on Puan Maharani's sentence structure was found to tend to use climax language style, (3 ) language style based on whether Puan Maharani was found to be dominant uses rhetorical language style. The special characteristics of Puan Maharani in her speech were reviewed from the pronunciation technique using tones and the tones used tended to be flat. Puan Maharani's expression is found to tend to be the expression that is displayed is not the same meaning of the sentence to be conveyed.